Preliminary assessment of structural masonry damage in Malbork Castle - Krzysztof Grzyb; Łukasz Drobiec; Jakub Zając; Kacper Drobiec (Case Studies in Construction Materials)
The castle in Malbork is one of the most representative brick buildings in the world and an excellent example of medieval defensive and residential architecture in Central Europe. This facility is a top-class monument, as evidenced by its inclusion on the UNESCO World Heritage List. Although it might seem that the subsoil is consolidated within the castle and no new cracks should be visible in the masonry structure - recent years have shown that the facility still requires both systematic monitoring of displacements and comprehensive structural diagnostics. Damage was observed in the Palace of the Grand Masters, particularly on the eastern wall and the barrel and palm vaults. The paper presents a preliminary analysis of palace damage and observed cracks. The assessment of the technical condition of the walls and the causes of the structural irregularities was carried out based on local inspections and tests of the structure, including geodetic measurements, ultrasonic tomograph tests and geophysical tests performed using the GPR method using the short-offset reflective profiling (GPR) technique. Additionally, destructive tests were also performed by drilling holes in the basement floor with the introduction of an inspection camera. It was found that the cause of the damage was uneven settlement of the subsoil. Additionally, it was found that there is probably a previously undiscovered brick vault below the basement floor, where visual inspection holes have been made.